THE USE OF SUNLIGHT FOR SUSPENSION OF SALT WATER WITH CONVERGEN CONVERSION LENS: THE USE OF SUNLIGHT FOR SUSPENSION OF SALT WATER WITH CONVERGEN CONVERSION LENS - Titik Koesdijati (Tibuana, 2018)
Salt in the main need for humans, In the process of shrinkage of salt products become the expected result is always increased because in the islands of Madura who have high salt income can be utilized. Light focus can be used through convex convex lens to increase sea water shrinkage so as to accelerate evaporation as well Get shrinkage of salt water salt raw material quickly. From observations made in May - June 2017 can be obtained data focusing light through convex convex lens is by focusing the sun on convex lens that is directed at sea water, so it can shrink the water faster. Acquisition of water depreciation using the tool obtained 95,000 cc / 95 liters, while 47.000 cc / 47 liters obtained from without tools. From this study it can be concluded that the value obtained yields a positive value, where the use of the tool from the volume of each volume filled 100 liters with a ratio of 1: 1 from the analysis obtained from using a tool faster 56% using tools with upper 14322.90 Of the 99% confidence interval received. So from the shrinkage using a faster tool, the depreciation of sea salt raw materials with convergent convex lenses can be applied directly as a technological reasoning.